Effect of Population Growth in Economic Growth in Nepal - Kunwar, Laxman Bahadur; Khadka, Birendra Singh (Journal of Economics and Management, 2023)
The study examined the relationship between the population growth and economic development issues in Nepal using time series data spanning from 1971 to 2021. The study adopted an ex-post facto research design and, obtained secondary data from the publication of the National Population and Housing Census 2021, National Report, Nepal. The data were analyzed using ordinary least square estimation technique. Descriptive and Analytical statistics tools are used to analyze the data. The findings of the study revealed that growth of the economically active population in agriculture, industry and service sectors significantly affect the Human Development Index measured by total GDP in Nepal. The research concludes that economically active population growth in these sectors have a positive impact in Nepal.